2010
DOI: 10.1080/10934521003709115
|View full text |Cite
|
Sign up to set email alerts
|

Water distribution systems as living ecosystems: Impact on taste and odor

Abstract: Six waters from different U.S. cities with known diverse taste and odor (TO) evaluations were selected for additional microbial characterization. All waters were subjected to microbial and cultural analyses, and four of the waters were further analyzed by cloning and sequencing of community 16S rRNA. The purpose of the study was to evaluate water distribution systems as living ecosystems, and the impact of these ecosystems on TO. All waters had total bacterial counts of at least 10(3) per ml. The water with lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…including A. lwoffii are known not just as opportunistic pathogens but also ubiquitous habitant in biofilm in water distribution systems. (Scott and Pepper, 2010;Vaz-Moreira et al, 2013;Kelly et al, 2014). This result suggests that inflammatory potency can increase with the regrowth of Acinetobacter sp.…”
Section: Comparison Of Inflammatory Responses Caused By the Purified mentioning
confidence: 75%
See 2 more Smart Citations
“…including A. lwoffii are known not just as opportunistic pathogens but also ubiquitous habitant in biofilm in water distribution systems. (Scott and Pepper, 2010;Vaz-Moreira et al, 2013;Kelly et al, 2014). This result suggests that inflammatory potency can increase with the regrowth of Acinetobacter sp.…”
Section: Comparison Of Inflammatory Responses Caused By the Purified mentioning
confidence: 75%
“…Additionally, Kalmbach et al (1999) reported that Aquabacterium commune is a dominant and ubiquitous community member in biofilms accumulated in several distribution systems in Hamburg, Berlin, Mainz, and Stockholm, which had different water sources and treatment processes. Acinetobacter lwoffii, which is known as an opportunistic pathogen, was also widely detected in water supply systems (Scott and Pepper, 2010). If these ubiquitously present bacteria, which have potent endotoxic activity, multiply in water distribution systems, significant elevations of endotoxin levels in water could occur.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, specific bacteria produce molecules affecting taste and odor of water. Typical examples are actinomycetes, which produce geosmin, responsible for an earthy-muddy water taste ( Srinavasan and Sorial, 2011 ), and bacteria involved in the sulfur cycle (e.g., sulfate reducing or oxidizing bacteria) that can promote a sulfur-based odor ( Scott and Pepper, 2010 ). Besides, yeast, fungi, and algae have also been recorded in drinking water and some of these organisms have been associated with taste and odor complaints ( Block et al, 1993 ; Sibille et al, 1998 ; van der Wielen and van der Kooij, 2013 ).…”
Section: Problems Associated With Bacterial Growth In Drinking Water mentioning
confidence: 99%
“…Bacteria are prokaryotic microorganisms that are the least complex of living microbes but offer the greatest metabolic flexibility and diversity. Bacteria can thrive within a variety of environments, including potable water distribution systems [ 1 ]. Despite deliberate disinfection of water via chlorine by utilities, almost all potable water within distribution systems can still contain vast populations of bacteria of up to 10 6 culturable cells per mL.…”
Section: Introductionmentioning
confidence: 99%